Central skills in toddlers’ and pre-schoolers’ mathematical development, observed in play and everyday activities - Reikerås, Elin (NOMAD Nordic Studies in Mathematics Education, 2016)
In good mathematical development, it is important to master some central skills at the kindergarten age. Being aware of such skills for each child is useful for facilitating children’s learning and development. The present study examines how kindergarten children master central mathematical skills in toddler age and preschool age. The staff in kindergartens collected data by using structured observation on the basis of observational material The Mathematics, the Individual and the Environments (MIO). The areas examined were Mathematical language, Logical reasoning, Shape and space, Pattern and order, Counting and series of numbers and Enumeration. The children were observed in play and everyday activities in kindergarten in two three-month periods when they were 2 1⁄2 years of age (toddlers, n = 1003) and two year later when they were 4 1⁄2 (pre-schoolers, n = 744). The results show a large dispersion in the children’s skills as toddlers, but as pre-schoolers, most of the children have a high level of mastery. The percentage of mastery at each of the observation times is reported and discussed in light of earlier findings. In our study, the children had slower development in the numerical area than was found in other research. Reflections about how the Norwegian kindergarten tradition and the method used to collect the data influence the results are included.